Cephalometric evaluation of molar distalization by hyrax screw used in conjunction with a lip bumper. - (:unkn) unknown (My University, 2006)
AIM: To determine the treatment effects of the Hyrax screw, when used with a lip bumper appliance, on the distalization of maxillary molars and the reciprocal effects on the anchor premolars and maxillary incisors. METHODS: Records, including study casts, lateral cephalometric radiographs, extra- and intraoral photographs of 9 patients were taken at the start of treatment and after distalization was achieved. Wilcoxon signed rank test was performed to analyze the skeletal and dental changes. RESULTS: During the active period of maxillary molar distalization, the maxillary incisors significantly proclined by 5.89 degrees (P <.05), 5.39 degrees (P <.05), and 1.72 mm (P <.05) relative to the SN, RH, and RV planes, respectively. The maxillary first molars showed significant distal crown tipping, as evidenced by 4.61-degree (P = .00), 4.17-mm (P = .00), and 1.11-mm (P = .02) decreases in U6-RH angle, U6 perpendicular RV, and U6 perpendicular RH distances respectively. Anchorage loss, with 4.17 mm mesial movement of the maxillary second premolars, was significant (P = .01). CONCLUSION: When selecting the appropriate method for maxillary molar distalization, anchorage loss potential, the need for patient compliance, and the duration of treatment should be considered.